Computational Muscle Driven Knee Simulator for Assessment of Total Knee Replacement Post-Cam Mechanics - Afzan Mohd Anuar, Mohd; Todo, Mitsugu (International Journal of Engineering and Technology, 2018)
Biomechanics of post-cam mechanism is essential in determining the longevity of knee implant. Computational knee simulator is an efficient method in characterizing TKA performance under various boundary conditions. The existing knee simulators, however, were actuated only by quadriceps translation and hip load to perform squatting motion. The present computational knee simulator was developed based on lower limb of Japanese female subject having body weight, W = 51 kg and height, H = 148 cm. Two different designs of PS-type knee prostheses were tested namely Superflex and NRG. The knee motion was driven by three major muscles; quadriceps, hamstrings and gastrocnemius. The biomechanical behavior of tibiofemoral articulation associated with post-cam engagement mechanics was observed. Post-cam engagement occurred at 80Â° and 65Â° of flexion angles for Superflex and NRG, respectively. Maximum von Mises stresses at tibial post were 80 MPa and 50 MPa for Superflex and NRG, respectively. The developed computational muscle driven knee simulator has successfully assessed the performance of TKA prostheses.Â